REINVENTING PENDIDIKAN ISLAM HARUN NASUTION - Sholehuddin, M. Sugeng (Forum Tarbiyah, 2010)
The world of Indonesian Muslim intellectuals rises afterHarun Nasution dared to build intellectual network that is rational,controversial and universal in relearn religious traditions as a renewaleffort in the world of Islamic education. Among the reform of Islamiceducation, Harun reconstructed the syllabus (not only fikh oriented,but more toward to the study of philosophy), teaching methodologies,scientific quality improvement, and simplification and improvementof the organization at UIN Syarif Hidayatullah Ciputat as well. Thus,Muslims would understand the knowledge of various aspects so it isnot only theological but historical and sociological empirical rooted ina neutral stance, critical and objective in understanding all the problemsthat exist in society